2022
DOI: 10.1111/pce.14425
|View full text |Cite
|
Sign up to set email alerts
|

Increasing temperature and vapour pressure deficit lead to hydraulic damages in the absence of soil drought

Abstract: Temperature (T) and vapour pressure deficit (VPD) are important drivers of plant hydraulic conductivity, growth, mortality, and ecosystem productivity, independently of soil water availability. Our goal was to disentangle the effects of T and VPD on plant hydraulic responses. Young trees of Fagus sylvatica L., Quercus pubescens Willd. and Quercus ilex L. were exposed to a cross-combination of a T and VPD manipulation under unlimited soil water availability. Stem hydraulic conductivity and leaf-level hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 87 publications
(115 reference statements)
1
34
2
Order By: Relevance
“…The below-ground component is another fundamental and understudied part of this continuum, with both woody and herbaceous species found to be sensitive to drought-driven declines in root hydraulic conductance ( K r ; Bourbia et al , 2021 ), and K r found to drive stomatal closure in olive ( Rodriguez-Dominguez and Brodribb, 2020 ). Air temperature and water content are also crucial during drought, with recent research finding that high temperature and high vapour pressure deficit can induce drought damage even in the absence of soil drought ( Schönbeck et al , 2022 ). Interdisciplinary research, such as the study by Thonglim et al (2023) , and an integrative, holistic perspective across disciplines are both vital in our efforts to characterize and accurately interpret the complex nature of drought tolerance and resistance across plant species.…”
Section: Understanding What Confers Drought Resistance: a Way Forwardmentioning
confidence: 99%
“…The below-ground component is another fundamental and understudied part of this continuum, with both woody and herbaceous species found to be sensitive to drought-driven declines in root hydraulic conductance ( K r ; Bourbia et al , 2021 ), and K r found to drive stomatal closure in olive ( Rodriguez-Dominguez and Brodribb, 2020 ). Air temperature and water content are also crucial during drought, with recent research finding that high temperature and high vapour pressure deficit can induce drought damage even in the absence of soil drought ( Schönbeck et al , 2022 ). Interdisciplinary research, such as the study by Thonglim et al (2023) , and an integrative, holistic perspective across disciplines are both vital in our efforts to characterize and accurately interpret the complex nature of drought tolerance and resistance across plant species.…”
Section: Understanding What Confers Drought Resistance: a Way Forwardmentioning
confidence: 99%
“…The recent paper by Schönbeck et al ( 2022 ) investigated the effect of rising VPD and temperature on plant hydraulics. The authors observed that VPD and temperature led to losses in stem hydraulic conductivity independently from soil drought.…”
mentioning
confidence: 99%
“…Significant losses in stem xylem hydraulic conductivity, up to about 75% in F. sylvatica and Q. pubescens , were observed. The authors concluded that ‘VPD and temperature can cause major hydraulic dysfunctions’ (Schönbeck et al, 2022 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations